Lessons Learned and Experiences Shared From the Front Lines: United Kingdom. Issue 6 (June 2020) - Wexner, Steven D.; Cortés-Guiral, Delia; Mortensen, Neil; Darzi, Ara
This is the second installment of a series of interviews, conducted by the senior author (S.D.W.) and the American College of Surgeons (ACS), that feature international leaders in surgery telling of the challenges they faced during the global COVID-19 pandemic. The disease arrived in the United Kingdom with devastating effects within a few weeks of its spread to Western Europe from China. In Oxford, Professor Neil Mortensen used his position as the President-elect of the Royal College of Surgeons of England to help coordinate efforts among the 4 Royal Colleges in the United Kingdom (his own, London, Edinburgh, and Ireland) to mobilize and retrain surgeons for duty helping to support in the critical care of patients with respiratory illness from the virus. In London, Lord Ara Darzi, a colon and rectal surgeon and leading innovator in minimally invasive surgery, underwent re-education himself in respiratory care to help his medical colleagues. As a member of the House of Lords involved in matters regarding the National Health Service as former Parliamentary Undersecretary of Health, he facilitated legislative measures to increase the physician workforce necessary to meet the demand for skilled personnel. Professor Mortensen and Lord Darzi have been recognized as honorary fellows of the ACS for their contributions to surgery. "Lots of people do not think it can possibly happen to them", Professor Mortensen said, "Our experience is that it will happen to you, and you cannot be prepared enough. Preparation, preparation, preparation is what you need to do."